On the purported "backbone fluorescence" in protein three-dimensional fluorescence spectra. Issue 114 (29th November 2016) - Bortolotti, Annalisa; Wong, Yin How; Korsholm, Stine S.; Bahring, Noor Hafizan B.; Bobone, Sara; Tayyab, Saad; van de Weert, Marco; Stella, Lorenzo
Abstract : A peak in 3D-fluorescence spectra of proteins, often assigned to backbone emission, is shown to be due to aromatic residues. Abstract : In this study, several proteins (albumin, lysozyme, insulin) and model compounds (Trp, Tyr, homopolypeptides) were used to demonstrate the origin of the fluorescence observed upon their excitation at 220–230 nm. In the last 10 years we have observed a worrying increase in the number of articles claiming that this fluorescence originates from the protein backbone, contrary to the established knowledge that UV protein emission is due to aromatic amino acids only. Overall, our data clearly demonstrate that the observed emission upon excitation at 220–230 nm is due to the excitation of Tyr and/or Trp, with subsequent emission from the lowest excited state ( i.e. the same as obtained with 280 nm excitation) in agreement with Kasha's rule. Therefore, this fluorescence peak does not provide any information on backbone conformation, but simply reports on the local environment around the aromatic side chains, just as any traditional protein emission spectrum. The many papers in reputable journals erroneously reporting this peak assignment, contradicting 5 decades of prior knowledge, have led to the creation of a new dogma, where many authors and reviewers now take the purported backbone fluorescence as an established fact. We hope the current paper helps counter this new situation and leads to a reassessment of those papers that make this erroneous claim.